Entrepreneurship Management at Al-Wathoniyah Islamic Boarding School (Manajemen Kewirausahaan di Pondok Pesantren Al-Wathoniyah) - Nur Alim (Institut Agama Islam Negeri (IAIN) Kendari, 2022)
This article aims to analyze: 1) entrepreneurial planning; 2) the implementation of entrepreneurship; and 3) entrepreneurship evaluation. The research was conducted at the Al-Wathoniyah Islamic Boarding School qualitatively with a narrative approach. Data obtained through observation, interviews, and documentation. The results of the study show that: 1) entrepreneurship planning at the Al-Wathoniyah Islamic boarding school is carried out by analyzing the factors of the needs of the Islamic boarding school by introducing entrepreneurial units that will be managed including: Cooperatives, Livestock, Plantations and Sewing Businesses. 2) the implementation of entrepreneurship at the Al-Wathoniyah Islamic boarding school is carried out by implementing such as instilling an entrepreneurial spirit, the students are taught direct practice by providing education and training in entrepreneurship skills. Education and training, especially entrepreneurship at the Al-Wathoniyah Islamic boarding school, which aims to make the santrii have the experience, skills and knowledge of entrepreneurship and inculcate entrepreneurial spirit in the students. Entrepreneurship education is carried out by non-formal channels. 3) entrepreneurship evaluation at the Al-Wathoniyah Islamic boarding school is carried out to determine the achievement of implementation results in each activity unit that has been exceeded. Then given directions from the management as well as views, guidance and motivation to the students to improve their skills.Keywords: Islamic boarding school management and entrepreneurship